2011
DOI: 10.3923/pjbs.2011.715.719
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Analgesic Effects of a Topical Herbal Mixed Medicine with Salicylate in Patients with Knee Osteoarthritis

Abstract: Knee osteoarthritis is the most common cause of disability among people and it is a common disease of joints that can lead to cartilage damage. In this study the analgesic effects of a herbal ointment containing cinnamon, ginger, mastic (Saghez) and sesame oil is compared with Salicylate ointment in patients suffering from knee osteoarthritis. It was a double-blind randomized controlled trail study. Patients with diagnosed arthritis were involved in the study and they were divided in two groups via block rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Ingredients were Zingiber officinale [36,42], Eurovita extract 33 [41], Zingiberis rhizoma [39], and EV Ext 77 [37], or dried, powdered ginger [38]. Different extracts of ginger were also combined (i.e., referred to as “ginger-plus” studies) with mastic and sesame oil [40], Zinaxin glucosamine [43,45], purified extracts of various plants [44], or multiple dietary ingredients [45]. Daily doses ranged from 250 to 1,000 mg/d (delivered as a capsule) and 6 g/d (delivered as an ointment) over three to 12 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ingredients were Zingiber officinale [36,42], Eurovita extract 33 [41], Zingiberis rhizoma [39], and EV Ext 77 [37], or dried, powdered ginger [38]. Different extracts of ginger were also combined (i.e., referred to as “ginger-plus” studies) with mastic and sesame oil [40], Zinaxin glucosamine [43,45], purified extracts of various plants [44], or multiple dietary ingredients [45]. Daily doses ranged from 250 to 1,000 mg/d (delivered as a capsule) and 6 g/d (delivered as an ointment) over three to 12 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Daily doses ranged from 250 to 1,000 mg/d (delivered as a capsule) and 6 g/d (delivered as an ointment) over three to 12 weeks. Ginger was compared with herbal [44], oral [43,44], and topical [40] pharmacologic interventions, or placebo capsules that were either undescribed [38,41,42] or contained maltodextrin [39], starch [36], coconut oil [37], or magnesium stearate [45]. Studies reported on outcomes including pain (N = 10), physical (N = 7) and global (N = 4) function, health-related quality of life (N = 3), and medication use (N = 1).…”
Section: Resultsmentioning
confidence: 99%
“…[28] Topical ginger (Z. officinalis) compress and pack reduced pain and fatigue and improved functionality and satisfaction in OA patients. [29] Herbal compounds are hypothesized to modulate several inflammation triggering factors, pathway mediators and conditions, thereby offering relief in such conditions. [30] In the current study, Upanaha Choornam showed a significant anti-inflammatory activity, comparable to that of standard analgesic Indomethacin.…”
Section: Resultsmentioning
confidence: 99%
“…Herbal therapies for OA can be divided into 2 main domains of oral and topical medicines, which were reviewed by The Cochrane Collaboration (36,37). In Iran, there is a special tendency toward the use of herbal remedies (10,38), and several studies have evaluated the efficacy of them for OA, both in vivo and in vitro (39)(40)(41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…We used sesame oil as an oily vehicle for active constituents of chamomile flower. Sesame oil has demonstrated anti-oxidant, anti-inflammatory (56) and anaesthetic activity (56), and beneficial effects in a compound herbal medicine for knee OA (43). In addition, sesamine as the major active constituent of sesame oil was evaluated and proved for its chondroprotective effects in OA model (58).…”
Section: Study Limitationsmentioning
confidence: 99%